A comparative study of elemental pollution and health risk assessment in urban dust of different land-uses in Tehran's urban area. (February 2020) - Mihankhah, Taraneh; Saeedi, Mohsen; Karbassi, Abdolreza
Abstract: Pollution levels of potentially toxic metals (PTMs) were studied performing enrichment factor, geo-accumulation index and ecological risk index. The most enriched elements which categorize as very high and extremely high enriched in different land-uses were in order of: commercial Cu (73.79)>Hg (66.55)>Pb (55.73)>Zn (46.15)>Cd (37.31); residential Pb (48.35)>Zn (34.79)>Cu (27.69)>Hg (22.96)>Cd (22.61) and industrial Zn (55.43)>Pb (51.52)>Cu (40.20)>Cd (26.29). In green lands sampling points, there weren't any elements with enrichment factor more than twenty. Based on the result of geo-accumulation index, commercial land-use appeared to be highly polluted with Cu, Pb and Zn. Residential land-use were highly polluted just in case of lead and industrial land-use were categorized as highly polluted in case of Zn, Pb and Cu. Hakanson's ecological risk index classified all of the land-uses except for green lands as very high ecological risk category. Factor analysis revealed that Cr, Mn, Ni, Fe and to a lesser extent Pb, Zn and As are from similar anthropogenic sources. Carcinogenic risk of Cr, Pb, As, Ni and Cd were found to be negligible for all land-uses for adult and children except for chromium in commercial land-use which exceed the safe level and need more attention in the future. Highlights: Pollution and health risk of PTMs in Tehran's urban deposited dust were studied. All land-uses except for green lands indicated very high ecological risk. Commercial land-use showed the highest concentration of PTMs. Concentrations of Pb, Zn and Cu in urban dust of Tehran were remarkable. Cancer risk of PTMs investigated in this study categorized in negligible level.